2012
DOI: 10.12968/ijpn.2012.18.8.407
|View full text |Cite
|
Sign up to set email alerts
|

Experiences implementing a 6-month pilot of a 7-day community CNS service in an urban hospice in Scotland

Abstract: The pilot demonstrated the need for a CNS service 7 days a week, and the service is now embedded in practice. Seven-day working benefits patients and families while being valued by the professional team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…A wide variety of study designs were used, with the most common being qualitative methods used in seven of the papers [32, 35, 36, 38, 41, 42, 50]. Four of the papers were service evaluations [30, 47, 51, 52] and there were three randomised controlled trials [34, 48, 49]. Three of the papers were protocols [29, 33, 45] and three of the papers simply gave a description of the intervention without any identifiable study design [39, 53, 54] which served to address objective 1 of the study (description of current telehealth use).…”
Section: Resultsmentioning
confidence: 99%
“…A wide variety of study designs were used, with the most common being qualitative methods used in seven of the papers [32, 35, 36, 38, 41, 42, 50]. Four of the papers were service evaluations [30, 47, 51, 52] and there were three randomised controlled trials [34, 48, 49]. Three of the papers were protocols [29, 33, 45] and three of the papers simply gave a description of the intervention without any identifiable study design [39, 53, 54] which served to address objective 1 of the study (description of current telehealth use).…”
Section: Resultsmentioning
confidence: 99%
“…While the process of designing and implementing the telephone advice line service was described in several studies 34, 37, 39, 40, 43, 44, 47, 50, 51 , PPI or stakeholder consultation was rarely mentioned and only two studies reported involving patients and carers during development and feasibility testing of services 34, 37 . Two further studies mentioned consulting key stakeholders during development but provided no detailed information on who or what this entailed 43, 47 .…”
Section: Resultsmentioning
confidence: 99%
“…In the seven studies that had 24/7 telephone advice lines and reported call data, between 19-69% of calls were received during out-of-hours periods 33, 35, 38, 43, 46, 52, 53 . Of these, most out-of-hours calls (35-78%) were received on weeknights before midnight, though the level of detail in reports differs 34, 36, 37, 3942, 44, 45, 4751 .…”
Section: Resultsmentioning
confidence: 99%
“…The relative proportion of out-of-hours palliative care research conducted into primary care, specialist palliative care and Emergency Department services point to the research interest and importance of each area to out-of-hours service provision. Whilst some specialist services have been designed to address specific needs of out-of-hours care, 52 , 59 , 83 , 113 primary care services clearly play a major and critical role in coordinating with secondary and tertiary care agencies to ensure continuity of care.…”
Section: Discussionmentioning
confidence: 99%
“…Specialist Palliative Care Service 47,48,68,69,74,80,86,94,[102][103][104][105][106][107]109,110 16 (20.8) Home visit 44,48,74,77,83,91,92,99,100,[102][103][104][105][106]112 15 (19.5) Triage Service (deliver via telephone or face-toface) 47,71,74,86,[91][92][93][102][103][104][105] 11 (14.3) Domiciliary Service 46,47,68,71,74,86,[91][92][93]…”
Section: Types Of Service N (%)mentioning
confidence: 99%